Evaluation of the Level of Variables Related to Allergic Rhinitis - Walaa Farouk Abbas; Mohammed Bahri Hassan (African Journal of Advanced Pure and Applied Sciences, 2023)
The study aimed to measure some biochemical variables in the blood serum of patients with allergic rhinitis. The study was conducted on (60) healthy and allergic rhinitis patients, their ages ranged between (10–60) years, and the study indicated that there was a significant increase at the probability level (p≤0.05) for the activity of the Lipoxygenase (LOX) enzyme in the blood serum of patients with allergic rhinitis of both genders. It also aimed to study the impact of oxidative stress on patients with allergic rhinitis and comparing it with the healthy ones, by measuring (14) variables of oxidation and antioxidants, also, measuring the enzyme activity. the results showed that there was a significant increase at the probability level (p≤0.05*) in the activity of (LOX) enzyme, malondialdehyde, glucose and uric acid in comparison with healthy people. Also, the results showed a significant decrease in the patients with allergic rhinitis in all antioxidants (vitamin C - vitamin D - vitamin E - bilirubin - albumin - globulin - glutathione - iron - total protein) compared to healthy people as a result of the increased oxidative stress. The effect of age, gender and blood type was also studied